Protocol for the PORT study: short-term perioperative rehabilitation to improve outcomes in cardiac valvular surgery – a randomised control trial - Lan Guo; Ji-yan Chen; Huan Ma; Haochen Wang; Jimei Chen; Yuanhui Liu; Haofeng Zhou; Fengyao Liu; Xuyu He; Mingyu Xu; Guolin Zhang; Xiangyu Cai (BMJ Open)
Introduction Perioperative rehabilitation (PORT) has shown a positive effect on patients undergoing cardiac surgery. However, there are minimal data on the impact of short-term PORT in cardiac surgery, which is associated with higher postoperative morbidity and mortality. The trial will assess the efficacy of short-term PORT in reducing in-hospital mortality, postoperative pulmonary complications and length of stay, compared with the usual care in cardiac surgical patients.Methods and analysis This is a single-centre prospective, randomised, open, controlled trial with a 1:1 ratio. Consecutive 800 adult patients undergoing elective valve surgery will be randomised to either usual care or in-hospital short-term PORT that consists of education, inspiratory muscle training, active cycle of breathing techniques and early mobilisation. The primary outcome of this study will be a composite of in-hospital all-cause mortality, incidence of postoperative pulmonary complications and the ratio of postoperative hospitalisation >7 days.Ethics and dissemination The PORT study was granted by the Medical Research Ethics Committee of Guangdong Provincial People’s Hospital in August 2018. Findings will be disseminated to patients, clinicians and commissioning groups through peer-reviewed publication.Trial registration number NCT03709511.